2004
DOI: 10.1159/000081106
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Immunoreactivity Reveals Nitric Oxide Production in the Electromotor and Electrosensory Systems of the Weakly Electric Fish, <i>Apteronotus leptorhynchus</i>

Abstract: Weakly electric fish produce electric organ discharges (EODs) used for electrolocation and communication. In the brown ghost knifefish, Apteronotus leptorhynchus, several neuron types in brain regions that control the EOD or process electrosensory information express nitric oxide synthase (NOS). The present study used immunoreactivity for L-citrulline, a byproduct of the production of nitric oxide (NO) by NOS, to assess NO production in NOS-expressing neurons. A polyclonal antibody against L-citrulline produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…In mammals, the diffusible messenger nitric oxide (NO) has been found necessary for the PF-LTP induced by 1 Hz PF stimulation alone (Lev-Ram et al 2002), while the presynaptic LTP generated by 4-Hz simulation requires an adenylate cyclase cascade involving activated PKA in PF terminals (Salin et al 1996). Studies in gymnotid fish have shown that the activity of the NO synthase-related enzyme NADPH-d (Smith et al 2005;Turner and Moroz 1995) and [ 3 H]forskolin-adenylate cyclase binding (Maler 1999) are both widely distributed in the cerebellar cortex, indicating that NO and PKA are potential factors in the cerebellar plasticity of teleosts. But again, it is unknown whether these molecules are expressed in the CLp or elsewhere in the mormyrid cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the diffusible messenger nitric oxide (NO) has been found necessary for the PF-LTP induced by 1 Hz PF stimulation alone (Lev-Ram et al 2002), while the presynaptic LTP generated by 4-Hz simulation requires an adenylate cyclase cascade involving activated PKA in PF terminals (Salin et al 1996). Studies in gymnotid fish have shown that the activity of the NO synthase-related enzyme NADPH-d (Smith et al 2005;Turner and Moroz 1995) and [ 3 H]forskolin-adenylate cyclase binding (Maler 1999) are both widely distributed in the cerebellar cortex, indicating that NO and PKA are potential factors in the cerebellar plasticity of teleosts. But again, it is unknown whether these molecules are expressed in the CLp or elsewhere in the mormyrid cerebellum.…”
Section: Discussionmentioning
confidence: 99%